تأثير التسويق المباشر السياحي في قرار اختيار السائح للوجهة السياحية بالجزائر -دراسة حالة عينة من مركبات العلاج الحموي بالجزائر- (مجلة الواحات للبحوث والدراسات, 2021)
This Study Aims To Identify The Reality Of Direct Tourism Marketing And Its Impact On The Decision To Choose The Therapeutic Tourism In Algeria And To Achieve These Goals Was Used Descriptive Analytical Method, The Study Population Will Be Tourists Who Have Come To The Red Sea Medical Tourism (Study Sample) During The Period Of Our Study, , And The Questionnaire Was Used As A Main Tool For This Purpose To Be Applied To The Sample Of The Study Consisting Of (556) Tourists, 500 Questionnaires Were Analyzed By (94.16%). A Sample Of 101 Employees Was Selected, And 77 (Questionnaire) Were Returned To The Final Analysis With A Recovery Rate (83.17%). To Analyze And Process Data Statistically, The Statistical Program (SPSS). The Study Found That There Is A Statistically Significant Effect Of The Independent Variable (Direct Tourism Marketing) In The Decision To Choose The Tourist, Therapeutic Tourism Complex , According To The View Of Both Tourists And The Management Of Tourist Complex(Sample Study). Keywords-  Tourism, Direct Tourism Marketing, Tourist Destination, Therapeutic Tourism, Tourist Decision.